Atom Probe Tomography investigations on grain boundary segregation in polycrystalline Ti(C, N) and Zr(C, N) CVD coatings. (15th March 2019) - El Azhari, Idriss; Barrirero, Jenifer; García, José; Soldera, Flavio; Llanes, Luis; Mücklich, Frank
Abstract: Atom Probe Tomography (APT) was used to obtain a direct evidence of chlor segregation and cobalt diffusion at the grain boundaries (GBs) of polycrystalline coatings deposited by moderate temperature chemical vapor deposition (MT-CVD) on a WC-Co cemented carbide substrate. Reasons behind segregations are discussed, and its effects are correlated to the micromechanical properties of Ti(C, N) and Zr(C, N). It is concluded that chlorine segregation is a relevant factor for explaining the low cohesive strength at the GBs of Ti(C, N) leading to intergranular failure during micro-compression testing, while its absence in Zr(C, N) along with Co diffusion contribute to grain boundary strengthening. Graphical abstract: Unlabelled Image